The reader - Schlink, Bernhard; Janeway, Carol Brown (New York : Pantheon Books, 1997)
Schoolboy Michael Berg, 15, meets an older woman and they have an affair, which she breaks off and disappears. Seven years later Berg, now a law student attending a trial, sees her in the dock, accused in a crime dating back to World War II and the death camp at Auschwitz. By a German writer.
Keywords: World War, 1939-1945 -- Atrocities -- Fiction; War crime trials -- Fiction; Germany -- Fiction; Love stories; Psychological fiction